Study of counseling activities of pharmacists in southern Khorasan province to patients in 2017 - mohammadali ghavami (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2019)
Introduction: The role and place of pharmacists 'services as one of the main pillars of the patients' treatment chain is definitely unhelpful. Research in this area suggests that pharmacist counseling leads to positive therapeutic outcomes and improves the quality of life, awareness of drug use, and patient satisfaction. This study was conducted to investigate the activities of pharmacists counseling in southern Khorasan province in 2017. Materials: and Methods: This is a cross-sectional descriptive-analytic study. The statistical population of the present study was two groups of pharmacies and patients. All 84 pharmacies operating in Southern Khorasan Province were included in this study. In this research, two main types of tools for recording counseling behaviors, views, and opinions were used. The first evaluation tool was taken by the patients at the pharmacy at each visit. The second tool was a questionnaire, which was adapted from a questionnaire made by Allajil and Al-Banemi in Saudi Arabia. In order to close the content of the questionnaire and obtain more accurate information, This questionnaire was first reviewed by the professors and consultants, and then it was adjusted and localized by two experienced pharmacists of South Khorasan,  Spearman, Kolmogorov-Smirnov, Kruskal-Wallis and Manviteni tests. Results: The results showed that there was a significant relationship between drug counseling and satisfaction rate of the patients in the 3rd and 4th scenario at level of .05. All the relationships between the amount of drug counseling and the patient's satisfaction with counseling were significant at each level of 0.05. There was an indirect relationshiop between scenarios one and two and direct linear relationship between scenarios three and four. Conclusion: Regarding the fact that the overall satisfaction of the patients from all scenarios is above 50%, it can be claimed that patients received a fairly good counseling.